Determinants of knowledge management behavior among academics - Mohamed Razi, Mohamed Jalaldeen; Habibullah, Md (IEEE, 2017)
The main focus of this work is to investigate the predictors of knowledge management (KM) behavior among university academics within the prevailing organizational climate. The KM behavior has been operationalized using SECI process (components of knowledge creation theory). A hypothetical research framework has been developed based on TRA, TPB and some related previous works. Survey based quantitative research approach was used. The data were collected using a self-administered questionnaire among 156 academic staff comprising different rank from a public university in Malaysia. After data screening, data reduction and reliability testing process, linear and stepwise multiple regression analysis were performed using SPSS. Though most of the hypotheses proposed were supported by linear regression analysis, only trust among colleagues and Effort expectancy of KM were emerged as the strong predictors of KM behavior according to stepwise multiple regression.